Cultural and Linguistic Obstacles for ELLs - Chenowith, Natasha H. (Beyond Words, 2014)
Abstract This qualitative study aims to assess which aspects of learning a second language English language, learners find challenging and to uncover the role that culture plays in learning a second languages as observed by the students themselves. Students were asked to make note of how cultural differences, assumptions, and biases have either enhanced or hindered the teaching and learning process. It was found that students experienced a sort of indirect marginalization or cultural â€œotheringâ€. Integration into the mainstream population of society, of the community, or even of the school was described as a major challenge for this particular group of students. Consequently, students had much difficulty achieving a comprehensive understanding of the language and surrounding culture.